PENGARUH GAYA MENGAJAR DAN PEMANFAATAN MEDIA PEMBELAJARAN ONLINE TERHADAP KEAKTIFAN SISWA DENGAN MEDIASI MOTIVASI BELAJAR PADA MATA PELAJARAN EKONOMI - Febiola, Syifa; Wibowo, Agus; Iranto, Dicky (Bhinneka Multidisiplin Journal, 2024)
This research aims to determine the influence of teaching style and the use of online learning media on student activity by mediating learning motivation in economics subjects. Data was collected using a questionnaire instrument which was analyzed using SmartPLS 3. The sample in this study was the entire population, as many as 145 student at SMAN 79 Negeri Jakarta. The results of this research show that teaching style has a positive and significant effect on student activity, teaching style has a positive and significant effect on learning motivation, the use of online learning media has no effect on learning motivation, the use of online learning media has no positive and significant effect on student activity, learning motivation has no effect on student activity, learning motivation has no effect or does not mediate teaching style or the use of online learning media on student activity